EVALUATION OF THE EFFECT OF THE LEVEL OF ROAD DAMAGE ON VEHICLE LOADS ON BALANCED ROADS : (Evaluasi Pengaruh Tingkat Kerusakan Jalan Terhadap Beban Kendaraan pada Jalan Lentur) - Assagaf, Sjaid S Fais (Uniqbu Journal of Exact Sciences, 2021)
The amount of load received depends on the weight of the vehicle, the configuration of the axle, the contact area between the wheels and the vehicle and the speed of the vehicle itself. This will give a value of damage to the pavement due to wheel axle loads that pass each time on the road. The weight of the vehicle is transferred to the pavement through the vehicle which is located at the ends of the vehicle axle. Each vehicle has a different axle configuration. The front axle can be a single axle of the wheel, while the rear axle can be a single, double or triple axle. From the background above, the problem formulation in this study is what is the volume of traffic that is traversed by vehicles on the roads studied, especially Siahoni Village and how is the level of damage to the hot mix road in Siahoni Village. The method used in this research is in addition to the survey method, direct observation also uses the PCI method where the data obtained, both secondary data and primary data, will be analyzed based on the PCI method so that the results are in accordance with the problems in the field to solve these problems according to the needs desired by the users or owners who have technical interests. The results showed that The discussion and results of the analysis above can draw conclusions regarding the analysis of road damage as follows: 1. The number of vehicles every day that pass through Siahoni Village with the formula above can be seen that every day the vehicles passing the Batuboy Village road to Siahoni Village are 580 vehicles / day 2. On the road there are fine cracks, collapsed, release of flea and crocodile skin with a density at Sta 08 + 800 = 5.82% in moderate condition, with a Deduct value of around 45, while the total damage is 11.95%.